2019
DOI: 10.3390/admsci9030050
|View full text |Cite
|
Sign up to set email alerts
|

Innovation for Sustainable Entrepreneurship: Empirical Evidence from the Bioeconomy Sector in Poland

Abstract: The growing importance of sustainable development, especially regarding environmental issues, contributes to shaping new trends at the level of enterprises. Sustainable development is perceived as a source of new entrepreneurial opportunities that serve to solve social and environmental problems. The main objective of this study is to identify factors supporting and hindering the development of enterprise innovativeness exemplified by the bioeconomy sector in Poland. A research analysis was based on the Entrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The sustainable entrepreneurship concept requires further research and interdisciplinary analyses of sustainable development. Much still needs to be done in shaping entrepreneurship as a dynamic process leading to sustainable socio-economic development (Sołtysik et al, 2019).…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustainable entrepreneurship concept requires further research and interdisciplinary analyses of sustainable development. Much still needs to be done in shaping entrepreneurship as a dynamic process leading to sustainable socio-economic development (Sołtysik et al, 2019).…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…Consequently, there is a need for global change towards an environmentalfriendly economy. An eco-friendly economy cannot be imposed from the top down but must be developed by entrepreneurs who react to policy incentives by implementing innovations in management and technology (Sołtysik et al, 2019). Therefore, we propose that: H1.…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…The innovation potential and competitiveness of small and medium-sized enterprises increases with the increasing level of the controlling management of the company, especially with a focus on the future results of the company (Pisar and Bilkova 2019). At present, companies are trying to achieve the goals of sustainable entrepreneurship and sustainable development, which are closely linked to ecological innovations, new values creation, and business transformation (Soltysik et al 2019). A study of micro-enterprises' innovation activities by Henley and Son (2020) showed that innovation did not increase company's productivity outcomes but increased company's exports, and thus their positive effect was reflected in the internationalization strategy of companies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some studies focused on the use of robots, nanotechnologies, sensors, blockchain and mobile applications. Therefore, studies using mobile platforms [128], automatic robot in the intelligent manufacturing process [129], robot-based reconfigurable fixture [130], smart partial least squares structural equation modeling (PLS-SEM) in the cement industry [131] or nanotechnology in the bioecoomy sector in Poland [132] were excluded. In addition, a publication focusing only on the optimization of the tree-echelon cold supply chain under cap and trade regulation in Industry 4.0 was excluded [133].…”
Section: Excluded Studiesmentioning
confidence: 99%